A qualitative study of recently bereaved people's beliefs about death: implications for bereavement care. Issue 9 (5th September 2013) - Draper, Peter; Holloway, Margaret; Adamson, Susan
<x xml:space="preserve">Abstract</x> Aims and objectives To investigate the beliefs of recently bereaved people about death and to explore the implications of these beliefs for bereavement care. Background Little is known about recently bereaved people's beliefs about death, although there is evidence that these beliefs may have an impact on health. The funeral provides an opportunity for bereaved people to reflect on their beliefs about death. Design A qualitative approach. Methods This paper describes one aspect of an interdisciplinary study of the spirituality of contemporary funerals. We obtained access to 46 funerals through funeral directors and other contacts, and interviewed principal mourners to explore their beliefs. Interviews were recorded, transcribed verbatim and analysed thematically. Results Three themes emerged that reflected the beliefs and experiences of bereaved people. The first theme describes people's understanding of death in terms of five positions: religious, dualist, eco‐spiritualist, materialist and death‐as‐transition. The second theme addresses a range of views about the possibility of life after death: resurrection, reuniting and reincarnation. The third theme describes ways in which people felt that their relationship with the deceased person continues after death: continuity as sense of presence and continuity as memory, legacy and love. Some people were reluctant to express a firm view about death. Conclusions People express a spectrum of beliefs about death. Their beliefs are infrequently linked to formal religious or spiritual perspectives but seem to have an important role in coping with bereavement. Relevance to clinical practice This is a unique study illustrating the complexity of bereaved people's beliefs about death. The study provides a research‐based framework within which to understand contemporary beliefs about death, and contributes to our understanding of how health professionals can support recently bereaved people.